Infections in neuromyelitis optica spectrum disorder. (January 2018) - Zhong, Xiaonan; Zhou, Yifan; Lu, Tingting; Wang, Zhanhang; Fang, Ling; Peng, Lisheng; Kermode, Allan G.; Qiu, Wei
Highlights: Summarizing the studies that either support or against the association between infections and NMOSD. Exploring the mechanisms by which infections may affect NMOSD. Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory astrocytopathy that has both genetic and environmental causes. A growing body of evidence suggests that the presence of several infectious agents correlates with the development of NMOSD. In this review, we summarize studies that either support or present evidence against the hypothesized association between infection and NMOSD. We will also present an overview of potential mechanisms underlying the pathogenesis of NMOSD. Finally, we provide some beneficial properties that infectious elements may have based on "hygiene hypothesis". It is of great clinical significance to further investigate the complex mechanisms by which infections may affect autoimmune diseases to develop better strategies to prevent and treat them, although so far no causal link between infectious agents and NMOSD has been established.